Efficacy of Some Herbicides on Growth, Tuber Production and Viability of Purple Nut-sedge (Cyperus rotundus L.)* (University of Khartoum Journal of Agricultural Sciences, 2023)
An experiment was conducted at the Sugarcane ResearchCenter, Guneid, during 2004/05 and 2005/06 seasons to evaluate theefficacy of some foliar herbicides on the growth of purple nutsedge(Cyperus rotundus L.) and to assess the effect of the treatments on theproduction and viability of tubers. The products tested were Krismat 75WG (Trifloxysulfuron-sodium+ametryn) at three rates (1.79, 2.38 and2.98 kg product ha-1 ) and Envoke 75 WG (Trifloxysulfuron-sodium) atthree rates (0.025, 0.030 and 0.035 kg product ha-1 ). Ametryn (Gesapax50 FW) + Atrazine (Gesaprim 50 FW) were used at the recommendedrates (3.81 L + 3.81 L product/ha), as a control. The results showed thatstatistically significant control of purple nut-edge was attained by allchemical treatments compared with the untreated check. Envoke 75 WGat 0.035 kg product/ha and the standard mixture of Gesapax + Gesaprimat its recommended rate significantly (P=0.05) reduced the number ofpurple nut-sedge compared with the untreated check. Gesapax +Gesaprim gave the lowest number of green leaves per plant. Envoke 75WG and Krismat 75 WG showed consistent reductions in tuberproduction and sprouting. Therefore, their successive application maylead to persistence and continuous reduction in the population density ofpurple nut-sedge in the fields of sugarcane.